ECOPRINT PADA KULIT DOMBA DENGAN WARNA PEWARNA ALAMI TEGERAN, TINGI, DAN SECANG - Sri Purwani (Jurnal Socia Akademika, 2023)
The purpose of this study was 1) to determine skin color after staining with natural dyes tegeran tingi and tujung. 2) to know the color of the prints of foliage and flowers produced on the surface of sheepskin. This type of research is qualitative descriptive research carried out with the method of Based Practice Research, experiments, supported by literature studies and documentation. The research subjects are eco print on sheepskin, while the object of research is natural dyes tegeran, tingi, secang. The results of the research that have been carried out are as follows; 1) From the eco print coloring experiment on sheepskin, sheepskin color after blanketing with natural dyes, natural dyes were obtained Tegeran absorbed sheepskin media resulting in skin color into a greenish crème, very light color and soft/soft; Tingi natural dyes absorbed sheepskin media produce skin color becomes ground brown/ clear brown color; and Secang natural dyes are absorbed by sheepskin media, resulting in a fairly clear pink skin color. 2) Print the color of the leaves and flowers produced on the surface of sheepskin in the form of knicker flowers whose orange color is printed like the original color; kenikir leaves print a yellowish-green color; Jatropha leaves print light / bright green on all three skin tones; jatropha leaves print a dark green color on the skin dyed tegeran and a lighter green on the skin that is colored high; red Panama leaves print a light blue color in high colors; biden leaves are printed in brownish-yellow on tegeran, secang, and light brown dyes on high coloring; And the green lanang leaves are coltan on the secang, the lanang leaves print a gray-green color on the tegeran color and a thin green on the high color. While the leaf spikes are only printed silhouettes of leaves in tegeran, tingi, and secang colors